KEPATUHAN PEDAGANG PASAR PADA HIMBAUAN PEMERINTAH TENTANG BAHAYA COVID-19 MELALUI PENDAMPINGAN BERBASIS TEKNOLOGI INFORMASI - Jamaluddin Hos; Sarpin Sarpin; Syaifudin S. Kasim; Megawati Asrul Tawulo; Darmin Tuwu; Harnina Ridwan (Jurnal Pengabdian NUSANTARA, 2021)
Corona virus outbreak (covid-19) is now not only a problem of the Indonesian people, but has become a global problem. The Indonesian government formally declared the corona virus outbreak (Covid-19) as a National Disaster through Presidential Decree Number 12 of 2020. A number of government appeals have been made regarding the handling of the covid-19 pandemic, the aim of which is to break the chain of transmission of the virus so that it does not spread large. Appeals include physical distancing, which was before social distancing or keeping a distance from others, wearing masks when leaving the house, always washing hands with soap. This paper seeks to describe the forms of market traders 'understanding of government appeals and market traders' adherence to government appeals after technology-based assistance through community service activities integrated with Thematic College Real Work (KKN). The results of the activity indicate that there has been a change in understanding among some market traders regarding the danger of co-19 so that it gave birth to compliance in the form of the use of personal protective equipment (PPE), especially for traders who have the ability to use technology in accessing information related to the covid-19 outbreak. Compliance has not been maximized for some traders due to the limited ability to use technology (social media) for most traders, so that access to information on covid-19 hazards and ways to overcome them are also limited. Based on these findings, intensive socialization is needed by involving various parties and utilizing various media.